2018
DOI: 10.3855/jidc.9733
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance, virulence genes and molecular subtypes of S. Enteritidis isolated from children in Shanghai

Abstract: # These two authors contributed equally to this work. AbstractIntroduction: Antimicrobial resistance of Salmonella poses a key threat to public health worldwide. Salmonella Enteritidis (S. Enteritidis) (119 isolates) from children under 10 years old with diarrhea in Shanghai from 2010-2012 were characterized for antimicrobial susceptibility, virulence gene profiles and pulsed field gel electrophoresis (PFGE) patterns. Methodology: The minimum inhibitory concentration for the 119 S. Enteritidis isolates was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…All (100%) S . Enteritidis isolates were resistant to at least one antimicrobial agent, which was higher than those reported from the Midwestern United States (50%), Spanish (61.7%), Serbia (22%) and Shanghai (77.3%) [2326]. Furthermore, a high proportion (81.0%) of MDR S .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…All (100%) S . Enteritidis isolates were resistant to at least one antimicrobial agent, which was higher than those reported from the Midwestern United States (50%), Spanish (61.7%), Serbia (22%) and Shanghai (77.3%) [2326]. Furthermore, a high proportion (81.0%) of MDR S .…”
Section: Discussionmentioning
confidence: 80%
“…PFGE genotyping can be used to ascertain the homology of the same serotype isolates [26]. Genetic diversity among S .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity of Salmonella involves different virulence genes, which contribute to the invasionand reproduction of Salmonella in a complex environment [ 13 ]. The invA , sseL , mgtC , siiE , and sopB genes were highly conserved and were genetic markers for the Salmonella pathogenicity island (SPI) in Salmonella [ 51 ]. The high prevalence of these virulence genes in our study also indicated widespread and highly conserved.…”
Section: Discussionmentioning
confidence: 99%